Recent results of molecularphylogenetic studies of endemic invertebrates inhabiting Lake Baikal - D. Yu. Sherbakov; M. V. Kovalenkova; O. O. Maikova (Вавиловский журнал генетики и селекции)
Lake Baikal and its invertebrates became a subject of systematic evolutionary studies more than a century ago. Exceptional taxonomic diversity of the lake’s fauna, high variability of habitats and large volume of auxiliary knowledge on the ecosystem enables one to study fine details of speciation mechanisms hardly accessible in other model systems. Parallel to the development of technological and methodological potential of biology most of new approaches were employed in studies of Lake Baikal. This review deals mostly with the results obtained during last two decades by means of molecular phylogenetics. The main common features found to date include, first of all, a relatively young age of the most recent common ancestor of the majority of species flocks. Second, it was found that almost all speciation events studied took place in sympatry and according to quite complicated scenarios. The latter is due to the fact that in the course of geological evolution of Lake Baikal there were no or very few episodes of its fragmentation sufficiently long for allopatric mechanisms to leave detectable traces. Reproductive barriers may temporarily disappear causing frequent mitochondrial or nuclear introgressions. As a result, intermediary forms of organisms of unclear taxonomic identity are a common occurrence. Another interesting feature is a practically absolute absence of evidence for co-evolution even of ecologically tightly connected organisms.